The Effect of Financial Technology (Fintech) and Financial Literacy on the Financial Behaviour of Millennials in Indonesia: The Mediating Role of Financial Attitude - Lidiana; Arsuni; Madrianah (Fakultas Ekonomi, Universitas Negeri Jakarta, Indonesia, 2024)
This study investigates the impact of Financial Technology (Fintech) and financial literacy on the financial behavior of millennials in Indonesia, with financial attitude acting as a mediating variable. As a global phenomenon, Fintech has revolutionized financial transactions through digital payments, online lending, investments, and personal financial management, significantly influencing millennials who are early adopters of these technologies. This demographic's responsiveness to Fintech results in reduced financial costs and improved financial management. Additionally, financial literacy and positive financial attitudes are crucial in shaping responsible financial behavior. This research highlights the necessity of understanding geographical, cultural, psychological, and social factors in the context of Fintech adoption and financial literacy, emphasizing the need for targeted educational programs and policies. Using a quantitative survey design with a sample of 300 Indonesian millennials aged 22-42, data was collected via online questionnaires and analyzed using Structural Equation Modeling (SEM). The findings reveal that both Fintech adoption and financial literacy positively influence millennials' financial behavior, with financial attitude significantly mediating the relationship between financial literacy and financial behavior. This study provides insights into enhancing financial literacy and Fintech adoption through effective education and public policies, contributing to better financial management among millennials.